Hubungan Efikasi Diri Terhadap Motivasi Belajar Pada Mahasiswa Fakultas Psikologi Universitas Prima Indonesia - Eltalina Tarigan; Diny Atrizka; Alfito CH Hutabarat; Suwandi Cipta Nugraha S; Chindy Novieandy Utami; Fikaria Br Tarigan (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The purpose of conducting this research is to test and analyze the relationship between self-efficacy and learning motivation in students of the Faculty of Psychology, Prima Indonesia University. The use of purposive sampling as a sampling technique, amounting to 279 active students of the Faculty of Psychology at Prima Indonesia University Medan. Research data collection utilizes a self-efficacy scale which includes 12 items and a learning motivation scale of 28 items. This study uses analytical techniques, namely Pearson Product Moment correlation. The results of this study show that self-efficacy has a positive and significant effect on learning motivation of 0.832 with a significant p = 0.000. Indicating that higher self-efficacy causes higher learning motivation as well.